The Development of Instruction Media in Accounting Using the Jātaka Story for Blended Learning in the 21st Century - Suksanguan, Wanrudee (Journal of International Buddhist Studies, 2018)
This experimental research aimed to develop e-Learning with Jātaka story instruction media in order to achieve the required criteria, to compare the outcome of learning using e-learning with the Jātaka story with the criteria 80, to compare pre- and post-learning outcomes, to study the useful moral teachings from e-Learning with the Jātaka story, and to analyze what the learners gained from learning using the Jātaka story. The sample group was 75 students from the Culinary Arts and Technology Program, Rangsit University, who registered in Accounting for Non-Accountants, S/2017. The students had self-study with e-Learning using the Jātaka story about the break-even point, and had two tests: pre-test and post-test, and completed the questionnaire. The statistics used for data analysis were mean and t-test. The findings showed that the efficiency of e-Learning with the Jātaka story met the required criteria: 81.60/80.65. The hypothesis testing revealed that the achievement during and after learning using e-Learning with the Jātaka story was 80, without the difference between the two tests. The top three moral teachings the learners implemented were: Mistake wrong for right; Land on your feet, and Gratitude, respectively. From learning with e-Learning using the Jātaka story, the first three benefits the learners gained were the use of information technology (96.00%), morals and ethics (90.67%), and creativity and imagination (86.67%).